"Family-bound" or "Pulled by Work"?—A Study of Chinese Women's Social Participation and the Factors Influencing It. (2nd January 2020) - Sheng, Li; Weirong, Ren
Abstract : On the basis of an analysis of data from the Chinese Social Survey (CSS) 2015, and with male social participation as the reference, we undertook an empirical study of Chinese women's current social participation and the factors affecting it along the two dimensions of "marriage and family life" and "employment and income status, " as well as the basic characteristics of individuals. Our findings show that in general women display a lower level of social participation than men. In terms of type of social participation, women are more likely to take part in policy-supported activities or serve as volunteers for public interest activities but less likely to participate in the activities of particular "action organizations" or the expression of opinion. Women's social participation is affected by many factors, including basic individual characteristics, marital status and family life, and employment and income status. A further gender comparison finds that female social participation tends to be more affected by marriage and family life, whereas male social participation is more closely related to employment and income status. We conclude that although more Chinese women have stepped out of the bonds of "home and family, " their social participation "outside the family" is family-bound in a way that is quite different that of men. Hence if we are to pursue gender equality at the level of social participation, it remains necessary to give women greater assurances in terms of marriage and family life by encouraging the realization of their self-worth and facilitating their social development, so as to coordinate and alleviate the double pressures of family and work, thus making women's social participation an important force and enhancing their all-round development.